Tax-Exempt Debt and the Capital Structure of Nonprofit Organizations: An Application to Hospitals - Wedig, Gerard J.; Hassan, Mahmud; Morrisey, Michael A. (Journal of Finance, 1996)
The availability of tax-exempt financing provides nonprofit (NP) organizations with their own tax-based incentives to issue debt. In this article, we develop a theoretical model in which NPs gain an indirect arbitrage from tax-exempt debt issuance, constrained by: 1) the requirement that fixed investment exceed tax-exempt debt flows (the project financing constraint), and 2) the constraint against share issuance. These constraints cause them to impute tax benefits to projects that afford access to the tax-exempt bond market. Empirical tests indicate that NP hospitals behave as if they have target levels of tax-exempt debt. Debt targeting is constrained by the availability of capital projects, while excess debt capacity stimulates investment.